2021
DOI: 10.1093/brain/awaa445
|View full text |Cite
|
Sign up to set email alerts
|

Severe oligomeric tau toxicity can be reversed without long-term sequelae

Abstract: Tau is a microtubule stabilizing protein that forms abnormal aggregates in many neurodegenerative disorders, including Alzheimer’s disease. We have previously shown that co-expression of fragmented and full-length tau in P301SxTAU62on tau transgenic mice results in the formation of oligomeric tau species and causes severe paralysis. This paralysis is fully reversible once expression of the tau fragment is halted, even though P301S tau expression is maintained. Whereas various strategies to target tau aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…These findings are consistent with a gradual increase in the intracellular steady-state expression level of the neurotoxic NH 2 htau we detected over time by Western blotting analysis on hippocampi from mice injected with STZ (3 mg/Kg) for 7, 14, 21 days (Figure S1). Besides, our biochemical results point out that the detrimental effects of toxic non-fibrillary tau species are reversible in vivo within a certain frame of time [90], when a biologically efficacy, therapeutic concentration of neutralizing antibody is reached.…”
Section: Discussionmentioning
confidence: 78%
“…These findings are consistent with a gradual increase in the intracellular steady-state expression level of the neurotoxic NH 2 htau we detected over time by Western blotting analysis on hippocampi from mice injected with STZ (3 mg/Kg) for 7, 14, 21 days (Figure S1). Besides, our biochemical results point out that the detrimental effects of toxic non-fibrillary tau species are reversible in vivo within a certain frame of time [90], when a biologically efficacy, therapeutic concentration of neutralizing antibody is reached.…”
Section: Discussionmentioning
confidence: 78%
“…Tau is a soluble protein acting as a microtubule stabilizer in neuronal cells [ 19 ]. It participates in the stabilization of microtubules, by binding to their surface, and fosters microtubules’ self-assembly [ 18 ].…”
Section: Protein Aggregates In Admentioning
confidence: 99%
“…Self-aggregation of tau and further recruitment of more tau monomers and dimers creates a nucleation center that harbors the process of oligomerization [ 23 ]. Tau oligomers then acquire a β-sheet structure, with subsequent aggregation into fibrils, culminating in the formation of NFTs [ 19, 20 ]. As observed for Aβ, intermediate species generated during the formation of tangles, are the most toxic ones affecting neuronal and synaptic function [ 20 ].…”
Section: Protein Aggregates In Admentioning
confidence: 99%
“…We have identified an association of K63-linked ubiquitin with pathological tau in postmortem AD brain tissues, particularly in the soluble fraction containing the most toxic oligomeric tau form (Fig. 7) [46][47][48], which has not been studied before. To identify the signature peptides of ubiquitination on tau oligomer, a combination of immunoprecipitation with a highly sensitive and specific mass spectrometry method using selected reaction monitoring (SRM) demonstrated that tau was ubiquitinated at microtubule-binding regions (MTBR) and the C-terminal domains including K254, K311, K353, K385, and K395 residues.…”
Section: Discussionmentioning
confidence: 86%